MEMAHAMI PENGALAMAN PEREMPUAN DALAM PENGGUNAAN AUGMENTED REALITY BEAUTY FILTER PADA PLATFORM INSTAGRAM - Geralda Mewengkang, Rafaela; Dwiningtyas Sulistyani, Hapsari; Ratri Rahmiaji, Lintang (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
The use of AR Beauty Filter is included in a new phenomenon that has emerged in postmodern society culture. Women as dominant social media users are also the largest users of AR Beauty Filter. With the advancement of technology, humans as creators of AR Beauty Filter have the freedom to create any filter they want. Therefore, the use of AR Beauty Filter can give women the freedom to show what kind of face I will be an expression of their beauty on social media. This study is a qualitative study with the interpretative phenomenological analysis or IPA method, which aims to understand women's experiences in using AR Beauty Filter on Instagram social media and how the meaning of the definition of beauty that arises from this experience, and whether women interpret beauty as a form of empowerment in self expression or as a way to meet conventional beauty standards. This study was conducted through in-depth interviews with six Indonesian female informants who actively use the Instagram application and the AR Beauty Filter feature. The results of this study indicate that women's experiences in using AR Beauty Filters have a significant role in underpinning the meaning of beauty that they consider ideal, and have become an essential need in sharing photo and video content on social media. The culture of life in the digital world that has become part of everyday human life, as well as the high intensity of AR Beauty Filter use, creates two self-images that are seen alternately continuously. These self-images are self-images in the real world (actual self) and self-images with AR Beauty Filters in the digital world (augmented/ideal self). The existence of these two self-images indirectly blurs the view of the real and the unreal (virtual/unreal) in women, especially regarding the reality of beauty. This is related to the concept of hyperreality put forward by Jean Baudrillard. It was found that the types and forms of AR Beauty Filters chosen and widely used by women still encode conventional beauty characteristics, which are not enough to empower women's beauty expressions on social media, and limit these expressions to only one particular standard.